Systematic reviews training for librarians: planning, developing and evaluating (Journal of EAHIL, 2018)
This article covers the content provided in a workshop offered at the EAHIL 2017 conference in Dublin, Ireland, titled “Systematic reviews: models of training for librarians.” Libraries are facing an increasing number of client requests for collaboration in conducting systematic reviews. Consequently, there is a high demand for librarians who are already skilled in this practice, accompanied by a desire to equip librarians who are less familiar with the skill-sets needed to conduct systematic reviews effectively. Several methods are available for consideration in training librarians, and this article focuses on the different components required by each method, so that libraries and librarians can better align training efforts with available library resources.